Longitudinal Stability of Interictal Spikes in Benign Epilepsy with Centrotemporal Spikes - Tenney, Jeffrey R. (Epilepsia, 2016)
OBJECTIVE: To describe the natural history of EEG changes in patients with Benign Epilepsy with Centrotemporal Spikes (BECTS) over 1 year. METHODS: Centrotemporal spikes (CTS) were visually evaluated based on 24-hour ambulatory EEGs to determine the total, left, right, and bilateral CTS while awake and asleep. These CTS rates were then used to compare the entire night of sleep to the first 2 hours of sleep, the repeatability of spike frequency over two recordings (done within days to weeks), and longitudinal changes in CTS rate over 6 and 12 months. RESULTS: 19 children with newly diagnosed and untreated BECTS were included in this analysis. An excellent correlation was found between the CTS rate during the entire duration of sleep and the first 2 hours of sleep (intraclass correlation (ICC) = 0.87, 95% CI = 0.67–0.95). An excellent correlation was also found between two recordings completed an average of 23 days apart while asleep (ICC = 0.92, 95% CI = 0.80–0.97) and lower, but still good correlation while awake (ICC = 0.70, 95% CI = 0.39–0.87). The average change in CTS rate between recordings at baseline and 6 months was a decrease of 64.7% (range −100% to +51.5%, p=0.01) and the average change in CTS rate between recordings at baseline and 12 months was a decrease of 57.7% (range −100% to +29.1%, p=0.01). Additionally, within 6 months, most children had decreased CTS rates with 30% of children being spike free. This absence of spikes did not continue in all children since the majority (60%) had some CTS at 1 year following diagnosis. SIGNIFICANCE: CTS rates during sleep are stable when compared over days to weeks, however, when comparing spike rates over months there is a larger degree of variability.